2017 8th International IEEE/EMBS Conference on Neural Engineering (NER) 2017
DOI: 10.1109/ner.2017.8008288
|View full text |Cite
|
Sign up to set email alerts
|

Influence of EEG tonic changes on Motor Imagery performance

Abstract: In Motor Imagery literature, performance predictors are commonly divided in four categories: personal, psychological, anatomical and neurophysiological. However these predictors are limited to inter-subjects changes. To overcome this limitation and evaluate intrasubjects performance, we tried to combine two groups of these measures: psychological and neurophysiological. As neurophysiological variables tonic changes in resting EEG theta and alpha sub-bands were considered. As psychological parameter we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…These studies showed that EEG based MI task-based training improved motor rehabilitation in stroke-patients and showed it be correlated with the fMRI based resting-state network [39]. In line with this, we also found improvement in BCI based MI performance shown in Supplementary Tables 2 and 3 in the experimental group of participants after five-days a week for four weeks, as shown in previous work [57]. More importantly, these effects are found in healthy participants.…”
Section: Discussionsupporting
confidence: 91%
“…These studies showed that EEG based MI task-based training improved motor rehabilitation in stroke-patients and showed it be correlated with the fMRI based resting-state network [39]. In line with this, we also found improvement in BCI based MI performance shown in Supplementary Tables 2 and 3 in the experimental group of participants after five-days a week for four weeks, as shown in previous work [57]. More importantly, these effects are found in healthy participants.…”
Section: Discussionsupporting
confidence: 91%